Applications of Pb isotopes in granite K-feldspar and Pb evolution in the Yilgarn Craton. (1st March 2022) - Zametzer, Andreas; Kirkland, Christopher L.; Hartnady, Michael I.H.; Barham, Milo; Champion, David C.; Bodorkos, Simon; Smithies, R. Hugh; Johnson, Simon P.
Abstract: The isotopic composition of Pb in a mineral or rock at the moment it formed – often referred to as common Pb – provides an important tool to track geological processes through time and space. There is a wide range of applications of common Pb isotopes including understanding magma sources, melt production, fractionation, contamination, and crystallization in the crust. Pb but not U is incorporated into the structure of K-feldspar during crystal growth, which, together with its widespread occurrence as a framework mineral, makes it an excellent common Pb tracer. Consequently, common Pb isotopes in granite K-feldspar crystals provide a potential signature of source composition and a link to crustal growth processes in the mid to lower crust. Hence, combining common Pb isotopes with Sm-Nd (or Lu-Hf) isotopic signatures from the same dated rocks allows assessment of the degree of isotopic communication from deep fractionation systems to those higher in the crustal column. In this contribution, we analyze common Pb isotopic signatures in K-feldspar from a granite sample transect through the Archean Yilgarn Craton in Western Australia. This transect crosses the major crustal-scale Ida Fault that is apparent on Nd and Hf isotopic maps and interpreted as a fundamental lithospheric boundary across which magma sources change. Our results yield a difference in median values of the Pb isotope derivative parameters µ ( 238 U/ 204 Pb) and ω ( 232 Th/ 204 Pb) across the Ida Fault, with higher µ and ω associated with more evolved Nd and Hf isotopic signatures on the western side of the fault. Pb evolution in the Yilgarn Craton is distinct from the widely applied Stacey & Kramers (1975) model. New Yilgarn-specific Pb evolution models are developed with implication for common Pb correction. A correlation in the spatial trends of granite K-feldspar common Pb signatures with those of upper crustal Pb ores and also the Sm-Nd and Lu-Hf systems reveals geochemical communication all the way through the crustal column, implying a common source for the entire lithospheric section on each side of the Ida Fault. Pb isotopes in granite K-feldspar are not an independent geochronometer but may yield important source context on major phase silicate growth that helps refine U-Pb geochronology interpretations (e.g., distinguishing magmatic versus metamorphic zircon growth).